Dark Energy Survey Year 1 results: measurement of the galaxy angular power spectrum. Issue 3 (3rd June 2019) - Camacho, H; Kokron, N; Andrade-Oliveira, F; Rosenfeld, R; Lima, M; Lacasa, F; Sobreira, F; da Costa, L N; Avila, S; Chan, K C; Crocce, M; Ross, A J; et al.
ABSTRACT: We use data from the first-year observations of the DES collaboration to measure the galaxy angular power spectrum (APS), and search for its BAO feature. We test our methodology in a sample of 1800 DES Y1-like mock catalogues. We use the pseudo- C ℓ method to estimate the APS and the mock catalogues to estimate its covariance matrix. We use templates to model the measured spectra and estimate template parameters firstly from the C ℓ 's of the mocks using two different methods, a maximum likelihood estimator and a Markov Chain Monte Carlo, finding consistent results with a good reduced χ 2 . Robustness tests are performed to estimate the impact of different choices of settings used in our analysis. Finally, we apply our method to a galaxy sample constructed from DES Y1 data specifically for LSS studies. This catalogue comprises galaxies within an effective area of 1318 deg 2 and 0.6 < z < 1.0. We find that the DES Y1 data favour a model with BAO at the 2.6 σ C.L. However, the goodness of fit is somewhat poor, with χ 2 /(d.o.f.) = 1.49. We identify a possible cause showing that using a theoretical covariance matrix obtained from C ℓ 's that are better adjusted to data results in an improved value of χ 2 /(dof) = 1.36 which is similar to the value obtained with the real-space analysis. Our results correspond to a distance measurement of DA ( z eff = 0.81)/ rd = 10.65 ± 0.49, consistent with the main DES BAO findings. This is a companion paper to the main DES BAO article showing the details of the harmonic space analysis.